Music‐supported therapy in the rehabilitation of subacute stroke patients: a randomized controlled trial. Issue 1 (1st April 2018) - Grau‐Sánchez, Jennifer; Duarte, Esther; Ramos‐Escobar, Neus; Sierpowska, Joanna; Rueda, Nohora; Redón, Susana; Veciana de las Heras, Misericordia; Pedro, Jordi; Särkämö, Teppo; Rodríguez‐Fornells, Antoni
Abstract: The effect of music‐supported therapy (MST) as a tool to restore hemiparesis of the upper extremity after a stroke has not been appropriately contrasted with conventional therapy. The aim of this trial was to test the effectiveness of adding MST to a standard rehabilitation program in subacute stroke patients. A randomized controlled trial was conducted in which patients were randomized to MST or conventional therapy in addition to the rehabilitation program. The intensity and duration of the interventions were equated in both groups. Before and after 4 weeks of treatment, motor and cognitive functions, mood, and quality of life (QoL) of participants were evaluated. A follow‐up at 3 months was conducted to examine the retention of motor gains. Both groups significantly improved their motor function, and no differences between groups were found. The only difference between groups was observed in the language domain for QoL. Importantly, an association was encountered between the capacity to experience pleasure from music activities and the motor improvement in the MST group. MST as an add‐on treatment showed no superiority to conventional therapies for motor recovery. Importantly, patient's intrinsic motivation to engage in musical activities was associated with better motor improvement.